Caregiver overload and factors associated with care provided to patients under palliative care - Alice Regina Felipe Silva (Investigación y Educación en Enfermería, 2021)
Objective To identify overload and associated factors among caregivers of adult patients receiving palliative care.Methods Descriptive, quantitative, and cross-sectional study addressing 40 adults under palliative care and their respective caregivers enrolled in the Home Care System in Ribeirão Preto, Brazil. Data concerning the patients included demographic profile and Mini-Mental State Examination. A form was used to collect the caregivers’ demographic data along with the Zarit Burden Interview Scale, Self-Reporting Questionnaire, Beck Depression Inventory, and Coping Strategies Inventory.Results Regarding the patients, 84.2% were women, 52.6% were over 80, 65.8% had no partner, and 76.3% presented cognitive impairment. The caregivers were mostly women (84.5%), aged 56.67 years old on average, were the patients’ children (42.5%); had no partner (55%), and lived with the patient (77.5%). The mean score obtained in the burden scale was 28.78 points, 32.5% had stress, and 42.5% depression. Regarding coping strategies, the ones most frequently used were positive reappraisal (12.8), withdrawal (10.2), and problem solution (9.7). A positive and statistically significant correlation was found between time spent with care (days and hours) and escape/avoidance with overload. Linear regression analysis revealed an association between being a woman (p=0.002), number of days spent with care (p=0.004), and depression (p<0.001) with overload.Conclusion Being a woman, spending more days providing care, and depressive symptoms were associated with caregiver overload.